Pembentukan Karakter Religius Melalui Kegiatan Pembiasaan Amaliyah Sebelum Tidur Di Pondok Pesantren Perkampungan Minang Kabau Al-Falah - Saputra, Indrian; Rehani, Rehani; Zainur, Muhammad (Journal Education And Islamic Studies, 2024)
Religious character is a conscious, planned, and directed process or method aimed at shaping an individual's attitudes and behaviors positively, adhering to the religious teachings they follow. This research aims to explore the formation of religious character among students (santri) at the Al-Falah Minang Kabau Village Islamic Boarding School, focusing on the practice of pre-sleep "amaliyah" rituals. Qualitative research methodology was employed, utilizing interviews and observations as data collection techniques. Findings indicate that the development of religious character in this boarding school is facilitated through habitual practices and imparting understanding of pre-sleep amaliyah rituals, by conveying the virtues or merits of each deed performed. The implications of this study provide deeper insights into the significance of amaliyah practices in shaping the religious character of students in Islamic boarding schools, and contribute to the advancement of religious education in similar institutions.